DR-UV/vis spectroscopy for studying the interaction of vanadium compounds with cellulose - Cakaj, Fatmir (2014)
Dissertação de mest., Qualidade em Análises, Faculdade de Ciências e Tecnologia, Univ. do Algarve, 2011